Effect of core-shell rubber toughening on mechanical, thermal, and morphological properties of poly (lactic acid)/multiwalled carbon nanotubes nanocomposites - Mohd Shaiful Zaidi, Mat Desa; Azman, Hasan; Agus, Arsad; Reza, Arjmandi (Wiley, 2019)
The effect of core-shell rubber (CSR) toughening on mechanical and thermal properties of poly(lactic acid)/multiwalled carbon nanotubes (PLA/CNT) nanocomposites were investigated. The nanocomposites were prepared by direct melt blending method in a counter‐rotating twin‐screw extruder. The contents of CSR were varied between 5 and 20 wt % while the content of CNT was kept at 5 phr. The extruded samples were injection molded into the desired test specimens for mechanical and thermal properties analysis. The impact strength of PLA/CNT increased with increasing CSR content with concomitant decrease in tensile strength and modulus. Interestingly, the flexural strength increased at low CSR content before decreasing at 15 and 20% content. Differential scanning calorimetry analysis on the second heating cycle shows no crystallinity content for PLA/CNT and all CSR toughened PLA/CNT nanocomposites, while thermogravimetric analysis shows lower thermal degradation of all CSR toughened PLA/CNT as compared to PLA/CNT nanocomposite. This study reveals significant correlation between CSR loading with the mechanical and thermal properties of the nanocomposites.